Low frequency of filaggrin null mutations in Croatia and their relation with allergic diseases. (18th October 2012) - Sabolić Pipinić, I.; Varnai, V. M.; Turk, R.; Breljak, D.; Kezić, S.; Macan, J.
Summary: Filaggrin gene ( FLG ) null mutations are considered associated with atopic dermatitis. This study was conducted to determine the prevalence of FLG null mutations R501X, 2282del4, R2447X and S3247X in the Croatian population and their role in the occurrence of allergic diseases including atopic dermatitis, allergic rhinitis, asthma and allergic contact dermatitis (ACD). Study enrolled 440 freshmen with defined allergic diseases by means of both present symptoms in International Study of Asthma and Allergies in Childhood questionnaire (relevant respiratory and/or skin symptoms) and markers of allergic sensitization (positive skin prick and/or patch test). FLG null mutations were successfully genotyped in 423 students of which 11 (2.6%) were carriers of FLG null mutation: 1/423 (0.2%) was heterozygous for R501X and 10/423 (2.4%) were heterozygous for 2282del4. No carriers of R2447X and S3247X mutations were identified. In wild‐type FLG carriers (412 subjects), atopic dermatitis was present in 45 (11%), allergic rhinitis in 70 (17%) and allergic asthma in 29 (7%) students. Twenty‐five of 393 (7%) patch‐tested wild‐type FLG carriers had ACD. Among 11 FLG null mutation carriers, four had one or more allergic diseases, and five had reported skin symptoms without defined allergic sensitization (positive skin prick test and/or patch test). FLG null mutations were not confirmed as a predictor of analysed allergic diseases, but were confirmed as an independent predictor of skin symptoms (OR 17.19, 95% CI 3.41–86.6, P  < 0.001). Our results in general indicate a low frequency of FLG null mutations in the studied Croatian population supporting a theory of a latitude‐dependent distribution of FGL null mutations in Europe, with a decreasing north–south gradient of R501X and 2282del4 mutation frequency. The relation between FLG null mutations and skin disorders was confirmed.